PRAKTIK INCOME SMOOTHING PADA PERUSAHAAN SEKTOR PERTANIAN DI BEI - Sumani Sumani; Ahmad Roziq; Widyastuti Annisa (EKUITAS (Jurnal Ekonomi dan Keuangan), 2021)
ABSTRACT The research objective is to examine the practice of income smoothing with several explanatory variables, namely: cash holding, political cost, profitability, and the board of commissioners. Income smoothing is an effort to normalize profits with the hope of increasing the company's market return. There are indications that agricultural sector companies are doing income smoothing. The population in this study were all agricultural sector companies listed on the IDX for the 2014-2019 period, with a purposive sampling technique, the number of samples used was 16 agricultural sector companies. Furthermore, the number of observed data was 96 data (6 years of observation in 16 agricultural sector companies). Methods of data analysis using logistic regression with α = 5% and α = 10%. The results showed that cash holding and profitability had no significant effect on income smoothing practices, both at α = 5% and α = 10%, but the political cost had a significant positive effect and the board of commissioners had a significant negative effect on income smoothing practices in agricultural sector companies. The implication of income smoothing practice with several explanatory variables can maintain the stability of the company's financial performance and will become an attraction for interested parties, however, income smoothing practise must go through supervision and consider some of the advice given by the board of commissioners. Key words: cash holding, board of commissioners, income smoothing, political cost, profitability ABSTRAK Tujuan penelitian adalah untuk menelaah praktik income smoothing dengan beberapa variabel penjelas, yaitu: cash holding, political cost, profitabilitas, dan dewan komisaris. Income smoothing merupakan upaya normalisasi laba dengan harapan untuk meningkatkan market return perusahaan. Perusahaan sektor pertanian terindikasi melakukan income smoothing. Populasi pada penelitian ini adalah seluruh perusahaan sektor pertanian yang terdaftar di BEI periode 2014-2019, dengan teknik purposive sampling, maka jumlah sampel yang digunakan adalah 16 perusahaan sektor pertanian. Selanjutnya jumlah data yang diobservasi sebanyak 96 data (6 tahun pengamatan pada 16 perusahaan sektor pertanian). Metode analisis data dengan regresi logistik dengan α = 5% dan α = 10%. Hasil penelitian bahwa cash holding dan profitabilitas berpengaruh tidak signifikan terhadap praktik income smoothing, baik pada α = 5% dan α = 10%, namun political cost berpengaruh signifikan positif dan dewan komisaris berpengaruh signifikan negatif terhadap praktik income smoothing perusahaan sektor pertanian. Implikasi praktik income smoothing dengan beberapa variabel penjelas dapat menjaga stabiitas kinerja keuangan perusahaan dan akan menjadi daya tarik bagi pihak-pihak yang bekepentingan, namun praktik income smoothing harus melalui pengawasan dan mempertimbangkan beberapa nasihat yang diberikan dewan komisaris. Kata kunci: cash holding, dewan komisaris, income smoothing, political cost, profitabilitas